2021
DOI: 10.3389/fvets.2021.723387
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Intestinal Health. In Vitro and Ex vivo Gut Barrier Models of Farm Animals: Benefits and Limitations

Abstract: Animal performance is determined by the functionality and health of the gastrointestinal tract (GIT). Complex mechanisms and interactions are involved in the regulation of GIT functionality and health. The understanding of these relationships could be crucial for developing strategies to improve animal production yields. The concept of “gut health" is not well defined, but this concept has begun to play a very important role in the field of animal science. However, a clear definition of GIT health and the mean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 146 publications
0
9
0
Order By: Relevance
“…12 It is important to note that there can be a large variation in TER values ranging from 50 to 8000 Ω*cm 2 for in vitro versus ex vivo studies, distinct cell lines, intestine from different species, as well as different regions of the intestine (e.g., jejunum vs. ileum vs. colon). 30 The only other research group to measure TER in tHIOs reported values ranging from approximately 90 to 280 Ω*cm 2 . 12 Here we report TER in tHIOs ranging from 14 to 43 Ω*cm 2 .…”
Section: Discussionmentioning
confidence: 99%
“…12 It is important to note that there can be a large variation in TER values ranging from 50 to 8000 Ω*cm 2 for in vitro versus ex vivo studies, distinct cell lines, intestine from different species, as well as different regions of the intestine (e.g., jejunum vs. ileum vs. colon). 30 The only other research group to measure TER in tHIOs reported values ranging from approximately 90 to 280 Ω*cm 2 . 12 Here we report TER in tHIOs ranging from 14 to 43 Ω*cm 2 .…”
Section: Discussionmentioning
confidence: 99%
“…In general, suitable in vitro models are of significant importance and many available in vitro studies assess specific subprocesses of gut functionality and interactions. A typical example are the gut barrier integrity models, for which the Caco-2 cell line is often described as “the gold standard”, even for animals, although it is derived from a human colorectal carcinoma [ 28 , 29 ]. However, similar models have also been described using species-specific cell lines, such as IPEC-J2, an intestinal epithelial cell line derived from the jejunum of a neonatal piglet [ 23 , 28 , 30 , 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…A typical example are the gut barrier integrity models, for which the Caco-2 cell line is often described as “the gold standard”, even for animals, although it is derived from a human colorectal carcinoma [ 28 , 29 ]. However, similar models have also been described using species-specific cell lines, such as IPEC-J2, an intestinal epithelial cell line derived from the jejunum of a neonatal piglet [ 23 , 28 , 30 , 31 , 32 ]. More complex models employ direct or indirect co-culture of different cell types, e.g., epithelial and immune cells, in order to better approximate the multilayers of in vivo gut processes.…”
Section: Introductionmentioning
confidence: 99%
“…The aim of this study was to explore the protective effects of several EO and powder extracts during an in vitro infection by E. coli F4 on Caco-2 cells, a recognized model for intestinal studies ( 27 ). In particular, we tried to elucidate the potential mechanism of action of all the tested compounds, to identify the most effective to maintain enterocyte's monolayer integrity by modulating the inflammatory response, reducing cellular susceptibility to the pathogen, and affecting ETEC adhesive properties.…”
Section: Introductionmentioning
confidence: 99%